PEMANFAATAN LIMBAH STYROFOAM SEBAGAI LOSS CIRCULATION MATERIAL PADA LUMPUR PEMBORAN PANAS BUMI - lia yu nita (KURVATEK, 2020)
Drilling mud is an important factor in drilling operations. drilling mud can function properly, if the mud is always controlled for its physical properties. This research, utilizing Styrofoam waste which is used as an additive in drilling mud in geothermal drilling to overcome Loss Circulation. The physical properties of sludge used as a controller to overcome loss circulation include specific gravity (density), viscosity, and filtration loss. The purpose of this study is to prove styrofoam waste that can be used as a Loss Circulation Material. The methodology used in this study is in accordance with American Petroleum Institute API 13A Standards. The sample used in the test uses four drill mud samples and three measurements. Sample 1 drilling mud without additives, second sample drilling mud plus additive 1 gram Styrofoam, second sample drilling mud plus additive 2 gram styrofoam second sample drilling mud plus additive 3 gram styrofoam Materials used include aquadest, bentonite and polished Styrofoam waste. The results of the addition of three gram styrofoam obtained a price density of 8.63 ppg, mud cake valued at 1.254 mm, a 13 ml filtrate volume per thirty minutes with a pH of 9 and meeting the API standard. loss of circulation material in geothermal drilling.Keywords: Styrofoam waste, drilling mud, loss circulation material, geothermal